Intake of Protein Hydrolysates and Phenolic Fractions Isolated from Flaxseed Ameliorates TNBS-Induced Colitis - e Silva, Fernanda G. D.; Paiatto, Lisiery N. [UNESP]; Yamada, Aureo T.; Netto, Flavia M.; Simioni, Patrícia U. [UNESP]; Tamashiro, Wirla M. S. C. (Wiley, 2018)
Scope: In the attempt to develop new therapeutic treatments for colitis, fractions containing phenolic compound isolate (Phi) and phenolic reduced-flaxseed protein hydrolysate (phr-FPH) from flaxseed are evaluated for their effects on the in vitro production of pro-inflammatory mediators and on the course of experimental colitis. Methods and results: The anti-inflammatory effects of Phi and phr-FPH from flaxseeds are studied in RAW264.7 cells and in trinitrobenzene sulphonic acid (TNBS) colitis model. It is observed that the incubation with Phi or phr-FPH result in lower levels of tumor necrosis factor α and nitric oxide in macrophages stimulated with bacterial lipopolysaccharide + interferon-γ. Prophylactic and therapeutic treatments with Phi and phr-FPH, respectively, greatly contribute to the prevention of weight loss and colon inflammation in colitic BALB/c mice. T cell proliferation, expansion of TH1 and TH17 cells, and pro-inflammatory cytokines are lower, whereas Treg cells are higher in spleen cell cultures from Phi-treated mice. In addition, therapeutic phr-FPH treatment is able to reduce the expansion of TH17 in splenic cell cultures. Conclusion: The consumption of phenolic and protein compounds extracted from flaxseeds has a protective effect on TNBS-induced colitis, and may be useful in the control of other inflammatory disorders.
Keywords: colitis; flaxseed; inflammatory bowel disease; peptides; phenolic compounds